INTESTINAL PARASITOSIS AND ITS INFLUENCE ON THE ONSET OF ANEMIA IN ELEMENTARY SCHOOL CHILDREN - Scarabotto, Gabriela Luiza; da Silva, Eduardo Sttocco; Veiga, Natan; Luz, Karine; de Souza, Julia Tristão; Locatelli, Claudriana (Seven Editora, 2024)
The incidence of intestinal parasitosis in poor locations is a problem for public health. The lack of basic sanitation, drinking water, correct food and adequate hygiene make parasitosis constantly present in vulnerable populations, leading to other diseases such as anemia, which negatively influence child development and the quality of life of adults. The objective of this study was to analyze fecal and blood samples from children at the Fita Bisol Municipal School, in the town of Imasa, in the municipality of Monte Carlo, Santa Catarina, in order to identify the presence of intestinal parasites and anemia. To better study the locality, data were obtained through a questionnaire applied to 30 families living in the neighborhood, containing questions about sanitary conditions. Fecal and blood samples were analyzed in the Parasitology and Hematology sectors of the Clinical Analysis School Laboratory of the Alto Vale do Rio do Peixe University. To instruct health education, folders with information on simple ways to prevent intestinal parasitosis were distributed. The results showed that 66.7% of the families eat raw food, 43.3% use untreated water, 46.7% have septic tanks and 50% have garbage collected by the city hall. Among the 24 stool samples collected, 16.66% had intestinal parasites, including Giardia lamblia, Entamoeba coli and Endolimax nana. The results of blood counts did not show any alterations. Inadequate hygiene and sanitation practices facilitate the transmission of parasites. Collection limited to one stool sample per patient, rather than three, represents a limitation to diagnostic accuracy. DOI:https://doi.org/10.56238/sevened2024.037-025